Service Quality, Organisational Culture, and Technology Acceptance Towards 1BestariNet Application In Northern Malaysia - Yeop Yunus, Nek Kamal; Kamarudin, Mohd Hafez; Zachariah, Tirzah Zubeidah; Md Zabit, Mohd Nazir (International Business Education Journal, 2016)
Since a decade ago, the Malaysian educational system has undergone a tremendous transformation due to recent technological advancement. To achieve the targets in the Malaysian Educational Blueprint, comprehensive usage of technology is crucial, not only in teaching and learning but also in management and administration. This study had been conducted using online administered questionnaires. About 80 secondary school teachers randomly selected in northern states of Malaysia, managed to complete all the questions in the questionnaires. The data collected were analyzed using SPSS and SmartPLS. It was found that organizational culture and technological acceptance influenced the 1BestariNet application but service quality did not. As such, this study had been conducted to fill in the gaps in previous research, especially in terms of the extent of the influence of service quality, organizational culture and technology acceptance on the 1BestariNet application. Future research directions were recommended at the end of the paper.